Nutritional status of schoolchildren and its distribution in Kuantan, Pahang: a preliminary study - Mat Ya, Roselawati; Mohd Abu Bakar, Wan Azdie; Afandi, Aflah; Mohd Hadzri, Siti Rokiah (2015)
To determine the prevalence of overweight and obesity among schoolchildren in Kuantan Pahang and to map the distribution. This community based cross sectional study was conducted in Kuantan, Pahang. Stratified random sampling method was used to select schoolchildren from seven subdivision of Kuantan district. A total of 253 schoolchildren age 13 years old were included. Data was collected using a questionnaire consisted of questions on socio demographic and anthropometry measurement. Schools’ coordinate were recorded and Geographical Information System (GIS) software was used to map and visualize the distribution of childhood obesity. The prevalence of overweight and obesity among the respondents was 15.8%, while normal and underweight were 75.5% and 8.7% respectively. Overweight and obesity was higher among females (8.7%) compared to males (7.1%). Overweight and obesity was also found higher in urban area (9.1%) compared to rural area (6.7%). However, there were no significant association between body mass index (BMI) with gender (p=0.391) and between urban and rural area (p=0.625). Both urban and rural area had similar percentage of underweight (4.3%). Conclusion: This study shows the prevalence of overweight and obesity among schoolchildren in this area as a major concern. The results warrant the need for further investigation to identify the root cause of childhood obesity in order to develop informed policy and guidelines.